2001
DOI: 10.1159/000048775
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic delineation of 2q37.3 deletion in autism and osteodystrophy: report of a case and of new markers for deletion screening by PCR

Abstract: Abstract.We recently studied a patient who meets criteria for autistic disorder and has a 2q37 deletion. Molecular cytogenetic studies were carried out using DNA isolated from 22 different 2q37 mapped BACs to more precisely define the extent of the chromosome deletion. We also analyzed 2q37 mapped polymorphic markers. In addition DNA sequences of BACs in the deletion region were scanned to identify microsatellite repeats. We describe four new polymorphic microsatellite repeat markers in the 2q37.3 region. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 25 publications
5
48
0
Order By: Relevance
“…20,23 Most of the patients in our study had heterogeneous behavioural disorders, with seven in the autistic spectrum, and patients P4 and P11 were reported as being autistic. The 'behaviour' map shows that all affected patients shared a deletion of the following candidate genes: TWIST2, HDAC4, 10 KIF1A, 15 PASK, 5 HDLBP, 5 FARP2, 5 and ATG4B. P14 (del/dup 2q37.3) showed normal behaviour but carried deletions of the same candidate genes, except for HDAC4 and TWIST2.…”
Section: Behavioural Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…20,23 Most of the patients in our study had heterogeneous behavioural disorders, with seven in the autistic spectrum, and patients P4 and P11 were reported as being autistic. The 'behaviour' map shows that all affected patients shared a deletion of the following candidate genes: TWIST2, HDAC4, 10 KIF1A, 15 PASK, 5 HDLBP, 5 FARP2, 5 and ATG4B. P14 (del/dup 2q37.3) showed normal behaviour but carried deletions of the same candidate genes, except for HDAC4 and TWIST2.…”
Section: Behavioural Disordersmentioning
confidence: 99%
“…Interestingly, P5 had a similar deletion but no behavioural problems. KIF1A, highlighted by the literature 15 and Manteia, encodes a motor protein involved in the anterograde transport of synaptic-vesicle precursors along axons, and a mutation in this gene has been reported in a patient with nonsyndromic intellectual disability (MIM 601255). KIF1A is also associated with hypoactivity and hyporesponse to tactile stimuli in knockout mice (Manteia).…”
Section: Behavioural Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate further diagnostic criteria for the 2q37 deletion syndrome, we compared the clinical findings of our patients and a representative cohort of other published patients carrying HDAC4 mutations or overlapping interstitial or terminal 2q37 deletions ( Figure 3, Table 1). 3,5,[15][16][17][18][19][20][21][22][23][24] The female to male ratio was 21/6. Regarding the body measurements, 4/18 of the patients were microcephalic, 8/24 revealed a short stature and 7/20 an overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that several cases of autism have been associated with chromosomal abnormalities such as deletion, duplication, balanced, unblanced and complex translocations (Yu et al 2002;Smith et al 2000;Thomas et al 1999;Vostanis et al 1994;Michaelis et al 1997;Nurmi et al 2001;Burd et al 1998;Ghazziuddin and Burnmeister 1999;Smith et al 2001;Gillberg et al 1991;Yan et al 2000;Vincent et al 2001;Tentler et al 2001;Wolpert et al 2001). Although in some cases deletions ranged from 5 to 260 kb and patients exhibited a varying degree of intellectual impairments (Bolton et al 2001a), there is no clustering of breakpoints involved and deletions are scattered throughout the genome.…”
Section: Cytogenetic Abnormalitymentioning
confidence: 99%